2004
DOI: 10.1063/1.1800283
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and magnetic properties of Nd60Fe30Al10 thin films

Abstract: In this letter we report results of the investigation of Nd60Fe30Al10 thin films prepared by electron-beam evaporation and studied by analytical transmission electron microscopy, x-ray diffraction, and magnetometry. Structural and magnetic characterizations show the existence of an amorphous matrix, which embeds a second glassy phase. The observed microstructure confirms the tendency of the Nd60Fe30Al10 system to show phase separation and to form an intrinsic composite as previously reported for slow-cooled bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Schneider et al attributed the intrinsic composite structure to a phase separation process taking place in the melt or the supercooled liquid state [55][56][57]. Sun et al shown the existence of two amorphous magnetic phases in melt-spun Nd 60Àx Y x Fe 30 Al 10 (x = 0, 10, 30) ribbons [66,67].…”
Section: Hard Magnetic Properties Of Nd(pr)-based Rebmgsmentioning
confidence: 96%
See 3 more Smart Citations
“…Schneider et al attributed the intrinsic composite structure to a phase separation process taking place in the melt or the supercooled liquid state [55][56][57]. Sun et al shown the existence of two amorphous magnetic phases in melt-spun Nd 60Àx Y x Fe 30 Al 10 (x = 0, 10, 30) ribbons [66,67].…”
Section: Hard Magnetic Properties Of Nd(pr)-based Rebmgsmentioning
confidence: 96%
“…Besides the paramagnetic phases, the grains boundaries, surfaces and magnetic inhomogeneities can play an important role as pinning sites of domain walls. The strong domain wall pinning mechanism (the pinning criterion is satisfied when: a » d 2 , where a is the lateral area of a single pin and d is the wall width [65]) has been proved in these Nd-based alloys from the temperature dependence of coercivity [55][56][57][58][59][60]69]. This is because that the condition of large impediments and narrow domain walls (small d) are easily favored by the inhomogeneous structure and the large RMA in the Ndbased alloys.…”
Section: Hard Magnetic Properties Of Nd(pr)-based Rebmgsmentioning
confidence: 98%
See 2 more Smart Citations
“…RE-TM films are required to have a single amorphous phase for their practical application [10]. It is known that the preparation of the single amorphous phase Nd-Fe film with high RE content is difficult because of phase separation induced by the positive mixing heat of Nd and Fe [11,12]. Therefore, in a previous study, an amorphous Pr(Fe,Co) film with low RE content was selected as the subject of research.…”
Section: Introductionmentioning
confidence: 99%